Neisseria meningitidis C114 contains silent, truncated pilin genes that are homologous to Neisseria gonorrhoeae pil sequences. - Perry, A C (1988)
Neisseria meningitidis pili can be classified into two groups: those (referred to here as class I pili) which are similar to gonococcal pili in that they react with monoclonal antibody SM1 and those that are dissimilar to gonococcal pili in that they lack the SM1-reactive epitope (class II pili). Pilus expression in N. meningitidis C114, a class II pilus-producing isolate, was investigated. The sole genomic segment of this strain that bore extensive homology with the pilE locus of Neisseria gonorrhoeae P9 was cloned in Escherichia coli. The production of the pilus structural subunit (pilin) from this meningococcal segment could not be detected by immunological and coupled in vitro transcription-translation analyses. Nucleotide sequence analysis revealed the presence in the C114 genome of two variant, tandemly arranged pilin genes (copies 1 and 2). Copies 1 and 2 are partial pilin genes that constitute part of a silent meningococcal pilin gene (pil gene) region, designated pilS. Both copies are truncated, corresponding to variable domains of the gonococcal pilE gene but lacking homologous N-terminal coding sequences. Located within sequences surrounding copies 1 and 2 were several classes of repeated elements that are associated with pil loci in N. gonorrhoeae.